Adaptation to floods: exploring coleoptile variability for flooding resilience of direct seeded rice during germination - Lupakisyo Mwakyusa; Newton Lwiyiso Kilasi; Richard Raphael Madege; Maria Cristina Heredia; Shalabh Dixit; Max Herzog (Cogent Food & Agriculture)
Variations in coleoptile elongation offer insights into rice adaptation to flooding stress during germination. Unfortunately, this trait remains understudied in African germplasms despite the prevalent direct seeding practice prone to floods. To address this gap, 44 rice genotypes, including anaerobic germination-tolerant and susceptible checks, underwent screening for coleoptile elongation after submergence in glass bottles. The Anaerobic Response Index (ARI) and Anaerobic Tolerance Index (ATI) were used, forming six clusters highlighting diverse elongation abilities. Cluster III, comprising genotypes NERICA 7, Kanamalia, Wahiwahi, Rojomena 271/10, Kubwa jinga, Faya mafuta, Mwasungo, and Ciherang Sub1 AG1 AG2, demonstrated potential for selection and adaptation to flooding, showing promising elongation characteristics. Positive correlations (0.675 for ARI, 0.66 for ATI) with anaerobic germination percentage underscored the link between elongation and germination. These findings not only advance our understanding of rice’s flood adaptability in Africa but also provide crucial breeding materials for enhancing direct-seeded rice resilience. Therefore, the promising genotypes identified in this study with enhanced coleoptile elongation mechanisms for surviving early floods following seeding are relevant for breeding initiatives aimed at increasing crop emergence and survival during these early flooding events. This resilience will ultimately enhance production and address food security challenges for farmers in flood-prone areas.